THE EFFECTS OF TAPING NEUROMUSCULAR COMPARE TO PHYSICAL THERAPIES MODALITIES IN PATIENTS WITH ADHESIVE CAPSULITIS OF THE SHOULDER - Sinaj, Enkeleda; Kamberi, Fatjona; Ndreu, Vjollca; Sinaj, Ermir; Nurka(Cina), Tatjana (European Scientific Journal, ESJ, 2015)
Adhesive capsulitis is a common painful condition characterized by severe loss of mobility and shoulder pain. Patients with this disease have a painful restriction of both active and passive mobility and an overall loss of shoulder movement in all planes. This experimental design study investigated the effect of combination of taping neuromuscular and stretching exercises program compared to ultrasounds and stretching exercises program. A total of 40 patients aged between 40 and 60 years were involved in the study. Patients were divided in two groups: first group subjected of neuromuscular taping +stretching exercises program for 4 weeks (experimental group 20 patients) and a second group subjected of a daily program of physical therapy + stretching exercises (control group 20 patients). They were evaluated using visual analogue scales for pain, goniometric measure for passive and active range of motion, SPADI index for shoulder function and patient satisfaction. Analysis showed statistically significant improvement in both the experimental and control groups. In addition, the mean improvement in VAS was significantly greater after first week in the experimental group than in the control group. The study showed that the combination of taping with stretching exercises program leads to better outcomes in rehabilitation of patients with frozen shoulder especially when an immediate effect is needed.